Design and realization of an ultra-low power sensing RF energy harvesting module with its RF and DC sub-components - Partal, Hakan P.; Belen, Mehmet A.; Partal, Sibel Zorlu (WILEY, 2019)
Herein, design, development, and analysis of ultra-low power sensing energy harvesting modules and their subcomponents for ISM band applications have been studied with a holistic approach in an effort to achieve a feasible and high efficient RF energy harvesting performance. The complete harvester system designed and developed here consists of a zero-bias RF energy rectifying antenna (rectenna), DC boost converters and energy storage super-capacitors. Compared with the counterpart energy sources, the surrounding or transmitted wireless energy has low intensity which requires designs with high efficiency. To achieve a successful harvester performance, rectifier circuits with high sensitivity Schottky diodes and proper impedance matching circuits are designed. Dedicated RF signals at various levels from nanowatts to miliwatts are applied at the input of the rectenna and the measured input power versus the scavenged DC output voltage are tabulated. Furthermore, by connecting the rectifier to a high gain antenna and using a RF signal transmitter, the wireless RF power harvesting performance at 2.4 GHz was tested up to 5 m. The performance of the rectenna is analyzed for both low-power detection and efficiencies. Impedance matching network is implemented to reduce the reflected input RF power, DC to DC converters are evaluated for their compatibility to the rectifiers, and super-capacitor behaviors are investigated for their charging and storage capabilities. The measured results indicate that a wide operating power range with an ultra-low power sensing and conversion performance have been achieved by optimizing the efficiency of the Schottky rectifier as low as -50dBm. The system can be used for battery free applications or expanding battery life for ultra-low power electronics, such as; RFID, LoRa, Bluetooth, ZigBee, and low power remote sensor systems.
Keywords: rectenna; RF energy harvesting; Schottky diode; ultra-capacitor; wireless power transfer; ANTENNA; Computer Science; Engineering